Meningkatkan Kreativitas Anak melalui Edukasi Seni dan Keterampilan di Desa Sinar Bhakti - Bella Widia Ningsih; Ajeng Tri Rezki; Dita Adelia; Natasya Ameilia; Hilmi Wiranawata (Jurnal Kabar Masyarakat, 2025)
Sports Enhancing children's creativity is an essential effort to support their holistic development. This community service program aimed to educate children in Sinar Bhakti Village through creative art and skill-based activities conducted at the kindergarten in Sinar Bhakti Village. The method used was a participatory approach, where children were encouraged to create art using simple and affordable materials. The program involved making collages in the shape of human faces and hair using colored paper and stationery, guided directly by the facilitators. The results of this program showed significant improvements in children's fine motor skills and creative thinking abilities. Additionally, the children became more confident in expressing their ideas through art. This activity also fostered positive social interactions among the children, creating a fun and inclusive learning atmosphere. The program serves as a practical example of how art-based activities can effectively support children's development, particularly in rural areas with limited resources.